Find the value of the expression "6y + 1" when y = 3

Question

Asked 5/9/2012 5:33:39 PM

Updated 10/13/2014 8:17:28 AM

10 Answers/Comments

This conversation has been flagged as incorrect.

s

Boyinbedroom|Points 249|

millizsen|Points 120|

raynelove04|Points 62|

arissa069|Points 171|

Boyinbedroom|Points 249|

bongche|Points 1875|

Question

Asked 5/9/2012 5:33:39 PM

Updated 10/13/2014 8:17:28 AM

10 Answers/Comments

This conversation has been flagged as incorrect.

Rating

3

Divide: (-6)/3

=-2/1

=-2

=-2/1

=-2

Added 6/30/2014 1:18:14 AM

This answer has been confirmed as correct and helpful.

3

Subtract: (-5) - 11

= 5+ 11

=-16

= 5+ 11

=-16

Added 6/30/2014 1:18:45 AM

This answer has been flagged as incorrect.

Flagged by yeswey [10/13/2014 8:16:15 AM]

3

Add 4/3+1/3

=4+3/1

=5/3

=4+3/1

=5/3

Added 6/30/2014 1:19:35 AM

This answer has been flagged as incorrect.

Flagged by yeswey [10/13/2014 8:16:46 AM]

3

6x + 3 = 27

6x = 27 - 3 = 24

x = 24/6 = 4

6x = 27 - 3 = 24

x = 24/6 = 4

Added 10/13/2014 8:13:03 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:14 AM]

3

when y = 3, 6y + 1 = 6(3) + 1 = 18 + 1 = 19

Added 10/13/2014 8:14:17 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:16 AM]

3

"three times some number is nine" into a Math statement is 3x = 9

Added 10/13/2014 8:15:01 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:28 AM]

3

x - 1 < 10

x < 10 + 1

x < 11

x < 10 + 1

x < 11

Added 10/13/2014 8:15:39 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:44 AM]

3

(-5) - 11 = -5 - 11 = -16

Added 10/13/2014 8:16:33 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:47 AM]

3

4/3 + 1/3 = (4 + 1)/3 = 5/3

Added 10/13/2014 8:17:28 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:48 AM]

How much money is 15% of $20? **Weegy:** 15* of 20 is 3 **User:** Translate the phrase "three times some number is nine" into a Math statement **User:** Solve the Inequality: x - 1 **Weegy:** C.) X **User:** Solve the Inequality: x - 1 9
x > 11
x **User:** Find the value of the expression "6y + 1" when y = 3 **Weegy:** y=2 **User:** Subtract: (-5) - 11 **User:** Solve for x: 3x - 2 = 2x - 1 **Weegy:** Answer is X=1;
solution:
3x - 2 = 2x - 1 ;
3x-2x=-1+2;
x=1 (More)

Question

Expert Answered

Updated 7/30/2014 7:28:11 PM

4 Answers/Comments

Three times some number is nine" translate into a Math statement is X*3=9.

Assuming that the number is X. X*3=9. x=9/3,x=3.

Assuming that the number is X. X*3=9. x=9/3,x=3.

Added 7/30/2014 7:24:43 PM

The answer for the Inequality: x - 1 < 10 is x<11.

x - 1 < 10

x<10+1

x<11.

x - 1 < 10

x<10+1

x<11.

Added 7/30/2014 7:25:54 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/30/2014 7:35:35 PM], Rated good by andrewpallarca

Simplify by using the Distributive Property and combining of similar terms: 5(x + 3) - 4(2x - 1)
- 3x + 11
- 13x + 19
- 3x + 19
3x + 19

Question

Updated 1/10/2018 8:24:24 PM

1 Answer/Comment

5(x + 3) - 4(2x - 1)

= 5x + 15 - 8x + 4

= -3x + 19

= 5x + 15 - 8x + 4

= -3x + 19

Added 1/10/2018 8:24:24 PM

This answer has been confirmed as correct and helpful.

31,438,563

questions answered

denyang

$462.55

Hearts 9,767 Views 1,882,953 Streams 584

sujaysen

$376.30

Hearts 7,958 Views 1,874,694 Streams 620

Flora1988

$338.00

Hearts 7,089 Views 2,262,825 Streams 705

miyaka

$325.90

Hearts 6,694 Views 2,887,878 Streams 876

PeachyStream97

$317.05

Hearts 6,676 Views 987,241 Streams 311

sampi1890

$315.05

Hearts 6,650 Views 3,282,408 Streams 897

maydj

$314.30

Hearts 6,619 Views 2,563,838 Streams 740

phpmicro

$244.70

Hearts 5,036 Views 1,862,897 Streams 508

There are no comments.